Increased Autophagy and Apoptosis in the Kidneys of Intrauterine Growth Restricted Rats. (4th May 2019) - Stewart, Tyrus; Kallash, Mahmoud; Vehaskari, V. Matti; Hodgeson, Sydney M.; Aviles, Diego H.
Abstract: Background: IUGR has been associated with nephron loss and chronic kidney disease (CKD). Materials and methods : We examined autophagy and apoptosis markers in the kidneys of IUGR Sprague Dawley rats induced by maternal low protein diet (LP), comparing them to controls. The autophagy marker LC3B, the pro-apoptotic protein Bax, and the anti-apoptotic protein Bcl-2 were determined by quantitative immunoblotting. Immunohistochemical expressions of LC3B, Bax, and Bcl-2 were evaluated at 4 weeks age. Glomerular counts (by maceration techniques) were performed at 5 weeks. Results : The LP diet offspring were lighter ( P  < 0.05). In IUGR kidneys, LC3B and Bax were increased at birth ( p  < 0.05, p  < 0.001) and at 4 weeks ( p  < 0.0142, p  < 0.0001), Bcl-2 was decreased at birth ( p  < 0.05), and there were less glomeruli ( p  < 0.01) at 5 weeks. Conclusions : Autophagy and apoptosis may have a role in IUGR associated decreased nephron number in Sprague rats.